Low-carbon investment portfolio management: a systematic literature review and future research agenda - Borges, Francine da Silva; Longaray, André Andrade; Dutra, Ademar; Ensslin, Sandra Rolim (Frontiers in Sustainability, 2026)
IntroductionThe green equity market has grown in tandem with environmental concerns, attracting increasing academic attention to best practices and the management of profitable portfolios in environmentally sustainable contexts. This study aims to identify the criteria and methods applied in the evaluation of low-carbon investment portfolios, while also presenting indicators from the main economic sectors and countries that have contributed to research in this field.MethodsA systematic literature review was conducted to analyze published studies on portfolio management in green contexts and their contributions to scientific knowledge. This approach enabled the identification of key criteria, methods, and the state of the art in this research domain.Results and discussionThe primary criteria include performance indices of listed assets, combined with companies’ sustainability and transparency practices. The most prominent evaluation methods were mathematical, particularly statistical and econometric methods. Academic concern with managing low-carbon investment portfolios has intensified since 2010, consolidating in 2015 with the Paris Agreement and indicating a trend toward greater application of bibliometric analysis.